Complement activation on endothelium initiates antibody-mediated acute lung injury - Simon J. Cleary; Nicholas Kwaan; Jennifer J. Tian; Daniel R. Calabrese; Beñat Mallavia; Mélia Magnen; John R. Greenland; Anatoly Urisman; Jonathan P. Singer; Steven R. Hays; Jasleen Kukreja; Ariel M. Hay; et al. (2020)
Antibodies targeting human leukocyte antigen (HLA)/major histocompatibility complex (MHC) proteins limit successful transplantation and transfusion, and their presence in blood products can cause lethal transfusion-related acute lung injury (TRALI). It is unclear which cell types are bound by these anti-leukocyte antibodies to initiate an immunologic cascade resulting in lung injury. We therefore conditionally removed MHC class I (MHC I) from likely cellular targets in antibody-mediated lung injury. Only the removal of endothelial MHC I reduced lung injury and mortality, related mechanistically to absent endothelial complement fixation and lung platelet retention. Restoration of endothelial MHC I rendered MHC I-deficient mice susceptible to lung injury. Neutrophil responses, including neutrophil extracellular trap (NET) release, were intact in endothelial MHC I-deficient mice, whereas complement depletion reduced both lung injury and NETs. Human pulmonary endothelial cells showed high HLA class I expression, and posttransfusion complement activation was increased in clinical TRALI. These results indicate that the critical source of antigen for anti-leukocyte antibodies is in fact the endothelium, which reframes our understanding of TRALI as a rapid-onset vasculitis. Inhibition of complement activation may have multiple beneficial effects of reducing endothelial injury, platelet retention, and NET release in conditions where antibodies trigger these pathogenic responses.